Bibliometrics approach to scientific communication structure - Pečarić, Đilda (Array, 2012)
Communication patterns are analyzed on the corpus of citation literature retrieved from doctoral dissertations in Information Science from 1978 to 2009 at Croatian universities. Scientific communication model is affected by institutional, language and time determinants ; thereby it is possible to accurately describe traditional distribution on primary, secondary and tertiary communication by quantitative methods. Analysis of 28, 188 cited bibliographic units by co-citation method resulted with network of clusters that matches scientific disciplines (archivistics, librarianship, museology, communicology, information science, information systems and lexicography). Alterations of key authors were observed according to time periods, affiliation to different scientific communities, cultural determinants, and functions in knowledge organization. According to the results of this analysis the conclusion can be drawn based on quantitative indicators: it is possible to recognize deep communication structure (conceptual knowledge zone, empirical knowledge zone, research front zone), beside organizational, communicational and intercultural determinants of knowledge exchange.